Ageusia associated to treatment with amitriptyline and terbinafine - Jerath, V. P.; Sood, Megha (International Journal of Basic & Clinical Pharmacology, 2017)
Ageusia is a rare condition characterized by loss of taste functions of the tongue. A large number of conditions may be responsible for causing ageusia. Adverse effects of drug therapy are the most common cause for the loss of taste. Ageusia can have a significant effect on the quality of life of patients and can lead to loss of appetite, weight, and may require discontinuation of drug administration in already compromised patients. We present two cases of ageusia one associated with amitriptyline in a patient with endogenous depression and the other with terbinafine in patient with tinea unguium.